(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to explore the dimensions of Green Education and its role in enhancing students’ psychological and social well-being, with a particular focus on improving the performance of social workers and psychological counselors within an integrated framework. The research problem stems from the gap between the theoretical vision of green education and its practical implementation, especially within the Libyan educational context, which faces challenges related to governance and infrastructure. The study adopted the descriptive-analytical approach through a review of scientific literature and documentary sources related to environmental psychology and the concept of green social work. The theoretical framework examined innovative concepts such as “psychological openness” and “problem recycling,” drawing on the Biophilia Hypothesis and Attention Restoration Theory to explain the innate relationship between humans and nature and its impact on reducing stress and anxiety. The findings revealed that green education extends beyond being merely an environmental activity to becoming a safe educational environment that contributes to reducing symptoms of depression, enhancing self-efficacy, and promoting students’ social empowerment. The results further indicated that integrating the roles of social workers and psychological counselors helps transform behavioral problems from administrative burdens into opportunities for innovation and productive environmental projects. The study also highlighted the need for sound educational governance and institutional partnerships in Libya to ensure the sustainability of initiatives and overcome resource limitations. A conceptual research equation was proposed: Sustainable Environmental Behavior = Psychologically Balanced Individual + Socially Adapted Individual This equation reflects the integration of psychological and social dimensions in fostering environmentally responsible behavior. Among the study’s key recommendations are the gradual integration of green education concepts into Libyan curricula, the establishment of “Green Innovation Corners” as platforms for channeling students’ energies, the activation of unified support teams under the supervision of specialized ministerial committees, and the utilization of modern technologies to enhance participation and positive engagement within the school environment.